Identification of Factors Affecting Construction Productivity in Pakistan Industry - Muneer Anees; Muhammad Saqib; Darya Memon (Sir Syed University Research Journal of Engineering and Technology)
Construction productivity is significant requirement which is point of focus for every construction manager. The main purpose of this study is to understand and highlight the factors which affect the labor productivity in Pakistan focusing Karachi which is the financial hub of the country. Karachi generates a big chunk of revenue and contributes to gross domestic product (GDP) of Pakistan. The main objective of this study is to identify the main factors affecting labor productivity of contractor, consultant and perspective of client. The data collection was carried out by one hundred sixty (160) questionnaire surveys. The results showed that feeble management and worst site conditions are solely responsible for degradation in both efficiency and output of the project.